Mathematical Model for the Equilibrium Flash Vaporization of the Nile Blend Crude Oil - Mahajoub, Imad E. A.; A. Gasmelseed, Gurashi; Babker, M. O.; O. Elsiddiga, Abdelbagi (Gezira Journal of Engineering and Applied Sciences, 2018)
Equilibrium Flash Vaporization (EFV) for the crude oil distillation is considered to be one of the crucial basis to simulate the true distillation operation in the distillation column. Classical procedures have been used to determine EFV of the crude oil, such as Maxwell and Edmister methods. Such methods are multi-graphical methods which are tedious and time consuming. Based on Maxwell graphical procedure, this paper is attempting to develop a new EFV mathematical model using experimental data from the Nile Blend crude oil. The developed model allows the process engineer to swiftly obtain the flash zone temperature of the Crude Distillation Unit (CDU) avoiding the tedious process of the graphical methods. Although the experimental data were taken from the Nile Blend oil, the same procedure could be followed to develop an EFV mathematical model for any other crude oil